International financial centres and development finance - Judith E. Tyson (Overseas Development Institute (ODI), 2019)
Economic growth in some of the world's poorest nations is being held back by a lack of financing. International financial centres (IFCs) have a crucial role to play in mobilising such finance as they can provide secure jurisdictions, fund structuring and tax neutrality for both private investors and public-private co-financing. The paper finds it is important that policy balance the trade-offs involved in fostering IFC intermediation of development finance, while ensuring that illicit activities continue to be tackled resolutely. It recommends the development community be more balanced in its approach to the debate on the possible advantages and disadvantages of utilising IFCs, to ensure the best possible outcome for the world's poorest nations.
Keywords: 330